Journal publishing in digital era: STM scientific journals in Croatia - Vrana, Radovan (Array, 2011)
This paper presents findings from the research of 87 journals in the fields of science, technology and medicine in Croatia. Journal publishing is a very demanding job and journal editors and editorial teams are facing many challenges such as insufficient financial support to the journal, low quality of article manuscripts, badly formatted article manuscripts, lack of help to the editor, etc. while doing their job. Journal editorial teams are doing their best to overcome these problems in order to facilitate transformation of scientific journals from paper based to electronic versions and to participate actively in scientific communication paradigm shift.